PENGARUH MONITORING HIPERTENSI BERBASIS APLIKASI TERHADAP KEPATUHAN MELAKUKAN TERAPI JUS PADA PASIEN HIPERTENSI - Faridah, Ida; Afiyanti, Yati; Huriyanah, Huriyanah (Nusantara Hasana Berdikari, 2022)
Hypertension is one of the non-communicable diseases and this requires very serious attention and needs to be taken nationally, where the prevalence is high and many individuals do not realize that they have hypertension, they know that they are suffering when they do a health check at the hospital. health services, because they feel pain or other complaints, hypertension is often called